ANALISIS PEMBIAYAAN SYARIAH PADA USAHA KECIL MENENGAH (UKM) DI BANK SYARIAH MANDIRI CABANG MALANG - Sri Budi Cantika Yuli (Intermediasi, 2009)
This research aims to analyze the financing distribution for small and medium enterprises (SMEs) in Mandiri Sharia Bank representative in Malang and further analyzing the debtor perception (SMEs) on the distribution of credit by Mandiri Sharia Bank representative in Malang. This research utilizing primary and secondary data. The data collection was conducted through questioner, interview, participative observation and literature review. Sample used in this research is 10 consumer of Mudharabah financing. Data was analyzed using qualitative descriptive analysis and scale analysis. The result shows that the distribution of credit to SMEs in Mandiri Sharia Bank representative in Malang is in accordance with the characteristics of Mudharabah financing asserted by National Sharia Board No. 07/DSN-MUI/IV/2000 regarding the requirement for financing, term and condition, and also Law on Mudharabah Financing. The perception of Mudharib regarding the credit provided by Mandiri Sharia Bank representative in Malang is excellent, undemanding and not time consuming.Keyword : Mudharabah Financing, SMEs, Mandiri Sharia Bank representative in Malang